Scalable synthesis of lotus-seed-pod-like Si/SiOx@CNF: Applications in freestanding electrode and flexible full lithium-ion batteries. (March 2020) - Zhang, Wenjie; Weng, Yuqing; Shen, Wanci; Lv, Ruitao; Kang, Feiyu; Huang, Zheng-Hong
Abstract: Intensive attempts have been devoted to solving the inferior cycling stability of Si-based electrode induced by the large volume change of Si. However, the complex synthesis procedures make many strategies much low practical significances. Together with the inferior cycling stability, an easy and scalable fabrication strategy is still a great challenge for implementing Si anode in commercial batteries. This work uses a simple water steam selective etching method to simultaneously engineer the pores and the confinement of commercial Si/SiOx in carbon paper electrodes, leading to a significant improvement in electrode flexibility and cycle life. The as-prepared freestanding lotus-seed-pod-like steam-etched Si/SiOx @CNF electrode shows a high capacity retention of 137% after 1000 cycles at 3 A g −1 . It also possesses outstanding electrochemical performance in a flexible lithium-ion full battery with LiCoO2 /steam-etched CNF as the cathode, even under bended condition. This simple approach may offer a pathway for the application of Si-based anode in commercialization and/or flexible energy storage devices. Graphical abstract: Image 1